Effect of a Leucine/Pyridoxine Nutraceutical on Caloric Intake and Body Composition of Obese Dogs Losing Weight - Murphy, Maryanne; Bartges, Joseph W.; Zemel, Michael B.; Kirk, Claudia A.; Witzel-Rollins, Angela (Frontiers in Veterinary Science, 2020)
The aim of this 29-week randomized, positively and negatively controlled study was to investigate whether a nutraceutical containing 1 g leucine and 13 mg pyridoxine can enhance weight loss while maintaining lean muscle mass in obese dogs. Twenty-four healthy, 2-year-old beagles were initially divided into obesification (n = 18) or ideal body weight groups (n = 6). After obesification, the eighteen dogs were divided into three weight loss groups and fed one of the following over 12 weeks: nutraceutical with canned adult diet (CAD; ObN), placebo with CAD (ObP), or a canned therapeutic weight loss diet (WLD). Dogs in the ideal body weight (IBW) group were fed maintenance calorie requirements with CAD over 12 weeks. Based on MANOVA, ObN and WLD lost similar amounts of total weight (3.4 +/- 0.6 vs. 4.4 +/- 1.1 kg, respectively) and fat mass (3.1 +/- 0.6 vs. 3.9 +/- 0.8 kg, respectively) after 12 weeks of treatment, and more than ObP (1.2 +/- 1.0 kg weight; 0.9 +/- 1.0 kg fat; p < 0.0001). These data show the nutraceutical is a promising option for successful weight loss in dogs. Maintenance levels of CAD were able to induce weight loss without risk of hypo- or anorexia, or the need to switch diets or restrict energy intake.